The effect of avian blood on Leishmania development in Phlebotomus duboscqi - Pruzinova, Katerina; Votypka, Jan; Volf, Petr (Parasites & vectors, 2013)
BACKGROUND: The development of pathogens transmitted by haematophagous invertebrate vectors is closely connected with the digestion of bloodmeals and is thus affected by midgut enzymatic activity. Some studies have demonstrated that avian blood inhibits Leishmania major infection in the Old World vector Phlebotomus papatasi; however, this effect has never been observed in the New World vectors of the genus Lutzomyia infected by other Leishmania species. Therefore, our study was focused on the effect of chicken blood on bloodmeal digestion and the development of Leishmania major in its natural vector Phlebotomus duboscqi, i.e. in a vector-parasite combination where the effect of blood is assumed. In addition, we tested the effect of avian blood on midgut trypsin activity and the influence of repeated feedings on the susceptibility of sand flies to Leishmania infection. METHODS: Phlebotomus duboscqi females were infected by rabbit blood containing L. major and either before or after the infection fed on chickens or mice. The individual guts were checked microscopically for presence and localization of Leishmania, parasite numbers were detected by Q-PCR. In addition, midgut trypsin activity was studied. RESULTS: Sand fly females fed on chicken blood had significantly lower midgut trypsin activity and delayed egg development compared to those fed on rabbits. On the other hand, there was no effect detected of avian blood on parasite development within the sand fly gut: similar infection rates and parasite loads were observed in P. duboscqi females infected by L. major and fed on chickens or mouse one or six days later. Similarly, previous blood feeding of sand flies on chickens or mice did not show any differences in subsequent Leishmania infections, and there was equal susceptibility of P. duboscqi to L. major infection during the first and second bloodmeals. CONCLUSION: In spite of the fact that avian blood affects trypsin activity and the oocyte development of sand flies, no effect of chicken blood was observed on the development of L. major in P. duboscqi. Our study unambiguously shows that sand fly feeding on avian hosts is not harmful to Leishmania parasites within the sand fly midgut.
Keywords: Chickens; Animal Feed; Gastrointestinal Tract; zvířata; Leishmania major; Female; Real-Time Polymerase Chain Reaction; králíci; krev; kvantitativní polymerázová řetězová reakce; Mice; Animals; Blood; gastrointestinální trakt; ženské pohlaví; Microscopy; mikroskopie; Rabbits; kur domácí; krmivo pro zvířata; myši; Phlebotomus